El posicionamiento de la imagen institucional del Gobierno Autónomo Descentralizado Municipal del Cantón Riobamba durante la pandemia del coronavirus, periodo marzo 2020 – agosto 2020. - Landi Álvarez, Ángel David (2022)
The objective of this research was to analyze the positioning of the institutional image of the Municipal GAD of Riobamba during the Coronavirus pandemic period March 2020 - In August 2020, knowing that the Covid-19 pandemic caused social networks to become a medium of mass communication, where the Municipal GADS had the task of generating information for public opinion, where the actions and work carried out during the health emergency were made known. The methodology that was used as an analytical method was descriptive, explanatory, and quantitative, with a non-experimental design. The population was made up of the city of Riobamba and four social communicators; the first sample was made up of 40% of the population since people who use social networks were considered, the second sample was non-probabilistic and intentional, the techniques were surveys and interviews, the instrument was the questionnaire, through which the collection, analysis, and interpretation of the data were generated. Allowed to conclude that it was identified that during the Covid-19 pandemic, the Municipality of Riobamba developed an external communication being of public opinion, the same that on several occasions was misrepresented, generating Fake news (false news) that came to generate controversy in the population and although it is taken into account that the pandemic was a new situation for everyone, since no one was prepared for an event of this type, there was a lack of strengthening in the strategies by the Communication Department of said organization.